Pengaruh Tingkat Pendapatan Wajib Pajak, Sanksi Pajak dan SPPT Terhadap Kepatuhan Wajib Pajak PBB-P2 - Fifi Nur Fitri Zakiyah; Susy Hambani; Yoyok Priyo Hutomo (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2025)
The rural and urban land and building tax (PBB-P2) is one of the potential and strategic taxes to be a source of regional income because the revenue from PBB-P2 is mostly used for regional expansion and improvement. Therefore, it is very important to make efforts to maximize PBB-P2 revenue. The realization of PBB-P2 in Bogor Regency in 2020-2023 continues to increase, but in contrast to the realization of PBB-P2 in Cigombong District, Bogor Regency in 2019-2023, there has been a drastic decrease. The purpose of this study is to find out the factors that affect the compliance of PBB-P2 taxpayers by including trust in the government as a moderation variable. The method used is quantitative with data analysis using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The number of samples in this study is 190 respondents. The results of the study showed that the level of taxpayers' income had no effect on the compliance of PBB-P2 taxpayers, while tax sanctions and SPPT had an effect on the compliance of PBB-P2 taxpayers. Furthermore, trust in the government is not able to moderate the influence of income levels, tax sanctions, and SPPT on the compliance of PBB-P2 taxpayers.